2013
DOI: 10.3109/17453674.2013.859421
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol- and lanolin-rich diets may protect against steroid-induced osteonecrosis in rabbits

Abstract: Background and purposeIt remains controversial how hypercholesterolemia influences the development of steroid-induced osteonecrosis (ON). We investigated the role of hypercholesterolemia induced by a cholesterol-rich diet on the development of ON in rabbits.Methods40 adult male Japanese white rabbits were randomly divided into 2 groups. 20 rabbits were maintained on a cholesterol-rich diet for 2 weeks before receiving steroid treatment (the CHOL group). The other 20 rabbits were maintained on a standard diet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Low-level evidence has shown protective effects of cholesterol-rich diets 149 , lipoic acid 150 , and enoxaparin for preventing disease progression 136 . Statins 142,151,152 , agents that target thrombosis and lipid deposition 153 , angiogenic and growth factors 154,155 , antiapoptotic factors 156 , herbal remedies 157 , and others 135,158-160 have been studied, but the results remain inconclusive.…”
Section: Nonoperative Therapymentioning
confidence: 99%
“…Low-level evidence has shown protective effects of cholesterol-rich diets 149 , lipoic acid 150 , and enoxaparin for preventing disease progression 136 . Statins 142,151,152 , agents that target thrombosis and lipid deposition 153 , angiogenic and growth factors 154,155 , antiapoptotic factors 156 , herbal remedies 157 , and others 135,158-160 have been studied, but the results remain inconclusive.…”
Section: Nonoperative Therapymentioning
confidence: 99%
“…All of these factors are important to consider when judiciously using steroids in the clinical setting. Zhao et al [82] and Kang et al [29] induced SONFH in male Japanese white rabbits with a single intramuscular injection of MPLS (20 mg / kg). The incidence of ONFH was 75% and 70% after two weeks respectively.…”
Section: Glucocorticoid Steroids Alone Modelingmentioning
confidence: 99%
“…There are also some studies that reported protective effects of lanosterol, pentosan, and pravastatin against ONFH 28,36,42) .…”
Section: Pt Aptt and Inr Resultsmentioning
confidence: 99%